The Democratic Constitutional State of Indonesia - Faiz, Pan Mohammad (Indonesia Law Review, 2011)
The political reform in Indonesia started in 1998 when President Soeharto was forced to resign from his presidential office after 32 years in power. This momentum has transformed Indonesian political culture from an authoritarian state to the third largest democracy in the world after India and United States. It also led to Indonesian constitutional reform which was marked by the amendments of 1945 Constitution for the first time in 1999.